Role of mitochondrial ribosome-dependent translation in germline formation in Drosophila embryos. - Amikura, R.; Sato, K.; Kobayashi, S. (Mechanisms of Development, 2005)
In Drosophila, mitochondrially encoded ribosomal RNAs (mtrRNAs) form mitochondrial-type ribosomes on the polar granules, distinctive organelles of the germ plasm. Since a reduction in the amount of mtrRNA results in the failure of embryos to produce germline progenitors, or pole cells, it has been proposed that translation by mitochondrial-type ribosomes is required for germline formation. Here, we report that injection of kasugamycin (KA) and chloramphenicol (CH), inhibitors for prokaryotic-type translation, disrupted pole cell formation in early embryos. The number of mitochondrial-type ribosomes on polar granules was significantly decreased by KA treatment, as shown by electron microscopy. In contrast, ribosomes in the mitochondria and mitochondrial activity were unaffected by KA and CH. We further found that injection of KA and CH impairs production of Germ cell-less (Gcl) protein, which is required for pole cell formation. The above observations suggest that mitochondrial-type translation is required for pole cell formation, and Gcl is a probable candidate for the protein produced by this translation system.